An Analysis of Moral Values in Encanto Movie Script - Maria Yunniosa Aska Putri; Yanti Sri Rezeki; Eka Fajar Rahmani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aimed to discover moral values presented in the Encanto movie script based on Hartmann’s theory and to identify the most dominant moral value of each group. The research method was a qualitative descriptive study. The data source was from the Encanto movie script by Charise Castro Smith and Jared Bush. The SPEAKING model (setting and scene, participant, end, act of sequence, key, instrumental, norm, and genre) by Dell Hymes was used as the data analysis to analyze conversation in the Encanto movie script. The findings showed 16 data on moral values divided into three groups of moral values. The first group was wisdom, courage, and self-control. The second group was brotherly love, trust and faith. The third group was radiant virtue. Moral values in this research provided relevant implications for other researchers in analyzing moral values through literary works, especially movie scripts.